Maturation-Dependent Differences in the Re-innervation of the Denervated Dentate Gyrus by Sprouting Associational and Commissural Mossy Cell Axons in Organotypic Tissue Cultures of Entorhinal Cortex and Hippocampus - Paul, Mandy H.; Hildebrandt-Einfeldt, Lars; Beeg Moreno, Viktor J.; Del Turco, Domenico; Deller, Thomas (Frontiers in Neuroanatomy, 2021)
Sprouting of surviving axons is one of the major reorganization mechanisms of the injured brain contributing to a partial restoration of function. Of note, sprouting is maturation as well as age-dependent and strong in juvenile brains, moderate in adult and weak in aged brains. We have established a model system of complex organotypic tissue cultures to study sprouting in the dentate gyrus following entorhinal denervation. Entorhinal denervation performed after 2 weeks postnatally resulted in a robust, rapid, and very extensive sprouting response of commissural/associational fibers, which could be visualized using calretinin as an axonal marker. In the present study, we analyzed the effect of maturation on this form of sprouting and compared cultures denervated at 2 weeks postnatally with cultures denervated at 4 weeks postnatally. Calretinin immunofluorescence labeling as well as time-lapse imaging of virally-labeled (AAV2-hSyn1-GFP) commissural axons was employed to study the sprouting response in aged cultures. Compared to the young cultures commissural/associational sprouting was attenuated and showed a pattern similar to the one following entorhinal denervation in adult animals in vivo. We conclude that a maturation-dependent attenuation of sprouting occurs also in vitro, which now offers the chance to study, understand and influence maturation-dependent differences in brain repair in these culture preparations.